2022
DOI: 10.4102/sajesbm.v14i1.461
|View full text |Cite
|
Sign up to set email alerts
|

Youth participation in agriculture, accounting for entrepreneurial dimensions

Abstract: Background: Despite the high youth unemployment levels, especially in sub-Saharan Africa, participation in the agricultural sector remains low. The agricultural sector provides valuable opportunities of employment, which could contribute towards relieving the high levels of unemployment and enhancing livelihoods of families in rural areas. Youth are also seen as the future of the agricultural sector and food production.Aim: To determine whether entrepreneurial dimensions, along with assets within the sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Yatma Guèye, of the Senegalese Ministry of Urban Renewal, Habitat and Living Condition argued that African cities are not just "centres of economic growth loaded with young people serving both as key players and mechanics in the development process", but concludes that managing this development involves prudent planning strategies. For example, Henning et al (2022) found in a study in South Africa that, although young people are heterogenous in their access to resources and capacities, those engaged in agricultural entrepreneurship actually believed in themselves and were more likely to take advantage of livelihood opportunities. This heterogeneity is strongly expressed by respondents in a Ugandan study of 'youth agripreneurs', experiencing the tension between representing a demographic category populated by a heterogenous group whose opportunities and challenges may not be defined as much by age as by other socioeconomic characteristics.…”
Section: Robert Kaplan Describes His Observations Of Visiting Several...mentioning
confidence: 99%
“…Yatma Guèye, of the Senegalese Ministry of Urban Renewal, Habitat and Living Condition argued that African cities are not just "centres of economic growth loaded with young people serving both as key players and mechanics in the development process", but concludes that managing this development involves prudent planning strategies. For example, Henning et al (2022) found in a study in South Africa that, although young people are heterogenous in their access to resources and capacities, those engaged in agricultural entrepreneurship actually believed in themselves and were more likely to take advantage of livelihood opportunities. This heterogeneity is strongly expressed by respondents in a Ugandan study of 'youth agripreneurs', experiencing the tension between representing a demographic category populated by a heterogenous group whose opportunities and challenges may not be defined as much by age as by other socioeconomic characteristics.…”
Section: Robert Kaplan Describes His Observations Of Visiting Several...mentioning
confidence: 99%